Process Protocol for Tilapia Fish Momos and its QualityEvaluation During Chilled Storage: Quality Evaluation of Tilapia Fish Momos - U., Parvathy; Sreepriya Prakasan; Sreelakshmi K.R.; Remya S.; Toms C. Joseph; Bindu J. (Fishery Technology, 2024)
Monosex tilapia is a widely cultured fish species in India on account of its capacity to adapt to varying culture conditions. However in India, the value addition options of this potential species are less explored leading to low market value for this species. This situation has created trading difficulties to the tilapia farmers and they are in search of options for better prize realization for this species. Present study aims to investigate the potential for more effective usage of tilapia through the preparation of value-added products and the assessment of its shelf life in chilled conditions (4oC). Momos are mince based products that are gaining more acceptance in the recent years. Dips are used as supplementary dishes along with momos which enhances its flavour. Protocols were standardized for the preparation of momos from tilapia and a dehydrated tomato-based dip was also developed. In the present study, the steamed momos had a moisture content of 53.99±1.05%, crude protein content of 31.11±0.20%, fat content of 9.38±0.37% and ash content of 0.91±0.06%. Fried momos indicated a moisture content of 43.36±0.46%, crude protein content of 29.67±1.54%, fat content of 16.09±0.69%, and ash content of 2.03±0.12%. The higher protein content in both the steamed and fried momos suggests its suitability as a healthy snack, especially for individuals who prefer seafood as a protein source. The TVBN values as well as oxidative parameters viz., TBARS of the samples gradually increased but were within the acceptability limit during the storage period. Storage study indicated a shelf stability of 10 days for fried momos and 13 days for steamed momos under chilled conditions (4oC). Present study suggests fish momos to be an ideal product to capture modern market on account of their superior nutritional profile, sensory quality and easiness in preparation.